2017
DOI: 10.1145/2998499
|View full text |Cite
|
Sign up to set email alerts
|

Semantics and Efficient Simulation Algorithms of an Expressive Multilevel Modeling Language

Abstract: The domain-specific modeling and simulation language ML-Rules is aimed at facilitating the description of cell biological systems at different levels of organization. Model states are chemical solutions that consist of dynamically nested, attributed entities. The model dynamics are described by rules that are constrained by arbitrary functions, which can operate on the entities’ attributes, (nested) solutions, and the reaction kinetics. Thus, ML-Rules supports an expressive hierarchical, variable structure mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…ese new algorithms are demonstrated on substantial case studies. is replicated computation report focusses on the ML-Rules modelling tool, and speci cally the new algorithms as demonstrated in the case studies in the paper [1]. e so ware was straightforward to install and use and the experimental results from the paper could all be reproduced.…”
Section: Replicated Computations Results (Rcr) Report For "Semantics mentioning
confidence: 99%
See 2 more Smart Citations
“…ese new algorithms are demonstrated on substantial case studies. is replicated computation report focusses on the ML-Rules modelling tool, and speci cally the new algorithms as demonstrated in the case studies in the paper [1]. e so ware was straightforward to install and use and the experimental results from the paper could all be reproduced.…”
Section: Replicated Computations Results (Rcr) Report For "Semantics mentioning
confidence: 99%
“…For the purposes of this replication report the focus was on the version of the ML-Rules tool corresponding to the paper [1]. e corresponding entry in the repository [4] provides the models which are used in the three presented case studies, the R scripts needed to create the plots and results as shown in the paper, as well as all the necessary so ware.…”
Section: Repeating the Results From The Papermentioning
confidence: 99%
See 1 more Smart Citation
“…ML-Rules allows the specification and simulation of complex systems biology models at multiple levels of organization. The semantics of ML-Rules is based on continuous-time Markov chains (CTMC) [34]. For all simulation experiments performed in this study, a stochastic simulator that is based on the Stochastic Simulation Algorithm (SSA) was used [34].…”
Section: In Silico Experiments: Modeling the Wnt/β-catenin Pathway Inmentioning
confidence: 99%
“…The semantics of ML-Rules is based on continuous-time Markov chains (CTMC) [34]. For all simulation experiments performed in this study, a stochastic simulator that is based on the Stochastic Simulation Algorithm (SSA) was used [34]. For the specification and execution of the model SESSL (The Simulation Experiment Specification on a Scala Layer) [35] was used.…”
Section: In Silico Experiments: Modeling the Wnt/β-catenin Pathway Inmentioning
confidence: 99%